Secondary electron emission from thin aluminum foils produced by high-energy electron beams - Karpus, S.H.; Kovalenko, G.D.; Kazarinov, Yu.H.; Dubina, V.M.; Kasilov, V.Y.; Kochetov, S.S.; Shopen, O.O.; Shliakhov, I.N. (Вопросы атомной науки и техники, 2021)
The description of the experimental equipment and technique for measuring the secondary emission of electrons (SEE) with application of accelerated electrons at the linear accelerator of the IHEPNP NSC KIPT with energies up to 30 MeV and a standard secondary emission monitor [1] are presented. Experimental data of secondary electron emission yields from thin aluminum targets (8 and 50 μm) for primary electron beam energies of 16 and 25 MeV have been experimentally measured. The analysis of the experimental data and their comparison with the theory are carried out. It is shown that the proposed technique for measuring the yields of secondary electron emission is useful and applied for study of low-energy and δ-electrons yields from thin foils, as well as to research the effect of the density effect depending on the energy of the primary electron beam. Надано опис експериментального обладнання та методики вимірювання виходів вторинної емісії електронів (ВЕЕ) при використанні пучка прискорених електронів на лінійному прискорювачі ІФВЕЯФ ННЦ ХФТІ з енергією до 30 МеВ і стандартного монітора вторинної емісії [1]. Отримано експериментальні дані по виходах вторинної емісії електронів з тонких мішеней алюмінію (8 і 50 мкм) для енергії первинного пучка електронів 16 і 25 МеВ. Проведено аналіз експериментальних даних і порівняння їх з теорією. Показано, що запропонована методика вимірювання виходів вторинної емісії електронів дозволяє отримувати дані по виходах низькоенергетичних і δ-електронів, а також дослідити вплив ефекту густини в залежності від енергії первинного пучка електронів. Приведено описание экспериментального оборудования и методики измерения вторичной эмиссии электронов (ВЭЭ) с использованием ускоренных электронов на линейном ускорителе ИФВЭЯП ННЦ ХФТИ с энергиями до 30 МэВ и стандартном мониторе вторичной эмиссии [1]. Экспериментально измерены выходы вторичной электронной эмиссии из тонких алюминиевых мишеней (8 и 50 мкм) при энергиях первичного электронного пучка 16 и 25 МэВ. Проведен анализ экспериментальных данных и их сравнение с теорией. Показано, что предложенная методика измерения выходов вторичной эмиссии электронов позволяет получать данные по выходам низкоэнергетических и δ-электронов, а также исследовать влияние эффекта плотности в зависимости от энергии первичного пучка электронов.